Highly soluble Cu(i)-acetonitrile salts as building blocks for novel phosphorus-rich organometallic-inorganic compounds12. Issue 45 (15th October 2018) - Elsayed Moussa, Mehdi; Piesch, Martin; Fleischmann, Martin; Schreiner, Andrea; Seidl, Michael; Scheer, Manfred
Abstract : The synthesis of the highly soluble salts [Cu(CH3 CN)3.5 ][FAlOC(C6 F10 )(C6 F5 )3 ] and [Cu(CH3 CN)4 ][AlOC(CF3 )3 4 ] is presented. These compounds react with polyphosphorus ligand complexes to form pristine phosphorus-rich Cu(i ) dimers. Abstract : The synthesis of the air-stable and highly soluble Cu(i )-acetonitrile salts [Cu(CH3 CN)3.5 ][FAl] (1 ) ([FAl] = FAlOC(C6 F10 )(C6 F5 )3 ) and [Cu(CH3 CN)4 ][TEF] (2 ) ([TEF] = AlOC(CF3 )3 4 ) is presented. Compound1 reacts with the organometallic polyphosphorus complexes [Cp2 Mo2 (CO)4 (η 2 -P2 )] (A ) and [(Cp*Fe(η 5 -P5 )] (B ) and salt2 reacts withB to form one new (3 ) and three unprecedented (4–6 ) phosphorus-rich Cu(i ) dimers with the general formulas [Cu2 (μ, η 1 :η 1 -A )2 (η 2 -A )2 ][FAl]2 (3 ), [Cu2 (μ, η 1 :η 1 -A )2 (η 1 -CH3 CN)4 ][FAl]2 (4 ), [Cu2 (μ, η 1 :η 1 -B )2 (η 1 -CH3 CN)4 ][FAl]2 (5 ) and [Cu2 (μ, η 1 :η 1 -B )2 (η 1 -CH3 CN)4 ][TEF]2 (6 ).